In vitro effects of the tyrosine kinase inhibitor, MAZ-51 in combination with epigallocatechin gallate on tumour survival in melanoma cells - Serem, June Cheptoo (University of Pretoria, 2024)
Dissertation (MSc (Anatomy))--University of Pretoria, 2024.